ANTI-INFLAMMATORY EFFECT OF NANGLAE AND PHULAE PINEAPPLE PEEL EXTRACT - Pongjanta, Anursara; Chansiw, Nittaya (Life Sciences and Environment Journal, 2019)
Inflammation is a process by which tissues respond to foreign organism infection. In the inflammatory process, an important inflammatory mediator was nitric oxide (NO), which causes swelling. Pineapples were an economically grown plant in Chiang Rai province. This study aimed to evaluate protein content, enzyme activity and anti-inflammatory activity of the extract from Nanglae and Phulae pineapple peel. The results showed that the extract of Nanglae pineapple peel had higher protein content and enzyme activity than that of Phulae pineapple peel, 4.56±0.56 mg/ml and 2.03±3.85 unit/ml, respectively. Both of pineapple peel extracts at the concentration of 0-1000 µg/ml did not show cytotoxicity effect in macrophage cells (RAW 264.7) which induced by lipopolysaccharide (LPS) for 24 hours. The analysis of NO inhibitory activity against standard aminoguanidine found that the extraction of Nanglae and Phulae pineapple peels inhibited the formation of nitric oxide, the strength varied depending on the concentration of the extracts. Therefore, both of the pineapple peel extracts showed good protein content, enzyme activity and anti-inflammatory activity. It’s can be used to prevent and treat diseases due to inflammation and other appropriate treatment.